Exploration of Primitive Nigerian Culture and Cross- Cultural Conflict in Chinua Achebe’s Things Fall Apart - Paudyal, Ganga Ram (AWADHARANA, 2022)
This article explores the portrayal of primitive Nigerian culture and conflicts created by the emergence of new culture as reflected in Achebe’s novel, Things Fall Apart. African society is full of rituals practices and it cannot accept any kinds of changes directly and the colonial influence has created many problems in that culture and many of its values are lost. During pre-colonial period the influence of colonial culture has created obstacles for the conservative practices and conflicts have occurred between new culture and traditional culture. It applies qualitative method for the study of primitive culture and the conflict between two cultures. To make textual analysis of the novel the concept the multiculturalism, cultural change and loss of culture are used as theoretical tools. As secondary sources, articles about the writer and his novels, cultural issues and cultural misunderstanding have been studied to find how traditional culture loses its value when new culture is introduced and how people struggle to preserve their primitive culture. The findings provide evidence that in process of cultural change conflicts occur and finally fresh and new culture emerges there.